Mesosaurid Swim Traces - da Silva, Rafael C.; Sedor, Fernando A. (Frontiers in Ecology and Evolution, 2017)
Despite subaqueous fossils tracks of tetrapods being quite common in the fossil record, few studies discuss their classification and morphofunctional interpretation. Despite their simple morphology, some important information about the trackmakers can be retrieved from these footprints. Subaqueous tracks were found in Brazil in the Irati Formation (Cisuralian, Permian), Paraná Basin, and described as Mesosaurichnium natans, related to Mesosauridae. The tracks were produced in a shallow marine environment, whose substrate contained crustacean shells forming a thin layer. The mesosaurids produced tracks by swimming close to the bottom. The propulsion was provided by undulatory moves of the long tail, mainly for faster swimming. The feet could act as accessory and slower propellants, but provided more maneuverability.